2022
DOI: 10.1186/s12866-022-02469-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and multidrug resistance of phylogenic groups B2 and D in InPEC and ExPEC isolated from chickens in Central China

Abstract: Background Avian colibacillosis is an infectious bacterial disease caused by avian pathogenic Escherichia coli (APEC). APEC causes a wide variety of intestinal and extraintestinal infections, including InPEC and ExPEC, which result in enormous losses in the poultry industry. In this study, we investigated the prevalence of InPEC and ExPEC in Central China, and the isolates were characterized using molecular approaches and tested for virulence factors and antibiotic resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…In this study, we found a positive correlation between phenotypic and genotypic resistance, as reported in several other studies [ 11 , 66 , 86 ], indicating the haphazard use of antibiotics and cross-contamination during farm practices. Genotype resistance to different antibiotics ( tetA , sul2 ) alone can predict the phenotype with higher sensitivity and specificity (85%–100%) in Salmonella [ 87 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found a positive correlation between phenotypic and genotypic resistance, as reported in several other studies [ 11 , 66 , 86 ], indicating the haphazard use of antibiotics and cross-contamination during farm practices. Genotype resistance to different antibiotics ( tetA , sul2 ) alone can predict the phenotype with higher sensitivity and specificity (85%–100%) in Salmonella [ 87 ].…”
Section: Discussionsupporting
confidence: 90%
“…A similar study conducted by Beattie et al (2020) reported that E. coli strains from manure isolates showed higher resistance to AMP and CTX. However, a lower resistance rate to AMK and GEN was also noted by Lu et al (2022) and Liu et al (2021) respectively. We noted the E. coli strains were susceptible to the "last resort" antimicrobials such as MEM, TIG, and CS, which is consistent with the findings of a study conducted by Hu et al (2019) in the human setting.…”
Section: Discussionmentioning
confidence: 83%
“…ST10 was widely detected in E . coli from other animals in China, such as pigs [ 73 ] and chickens [ 74 ], indicating that ST10 may be the prevalent ST in E . coli strains from animals in China.…”
Section: Discussionmentioning
confidence: 99%